RANCANG BANGUN ALAT KESELAMATAN LALU LINTAS MENGGUNAKAN ARDUINO UNO - ramadhan, nico; Rosiska, Evan (Computer Science and Industrial Engineering, 2021)
The development of technology at this time is arguably quite high, especially in the microcontroller and the design of home and traffic security, many developed countries have implemented technology in their traffic systems. Therefore, traffic in Indonesia needs to use additional technological devices to make the effectiveness of signs more efficient and functioning properly, starting from the pedestrian security system on the zebra cross, the method used is a flowchart, which consists of requirements, design, implementation, testing. , maintenance, the result of this study is to design a safety device for zebra cross users.